2018
DOI: 10.1016/j.aninu.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme activity and phosphate uptake in the small intestine of Sprague Dawley rats improved by supplementation of infant formula with prebiotics

Abstract: This study was to identify the effects of prebiotics supplemented in infant formula on enzyme activity and phosphate uptake in the small intestine of Sprague Dawley (SD) rats. Forty-eight healthy SD rats at 15 days old (a week before weaning) with similar weight were randomly divided into 3 groups: A (control group), B, C, with 16 rats per group. Rats in groups A, B, C were fed a standard infant formula, the standard infant formula supplemented with oligosaccharides, and the standard infant formula supplemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…It was observed that as compared to group A, group B and C showed the following: (1) In SD rats group C showed greater activities of sucrose and lactase in the small intestine; (2) In SD rats of group C comparative expressions of lactase gene in the anterior and posterior segments of the small intestine were increased by 1.68 and 2.26, and the Mgam gene relative expression in the posterior segment of the small intestine was improved by 0.99 in SD rats of group C; (3) the relative expressions of Na/Pi-IIb gene in the anterior and posterior segments of the small intestine were increased by 1.85 and 2.28 in SD rats of group C. These results specify that the supplementation of prebiotics in infant formula can stimulate enzyme movement in the small intestine by improving the relative expression of enzyme gene and Na/Pi-IIb gene and by reducing the intestinal injury. The polysaccharides improved to be healthier than that of oligosaccharides [124].…”
Section: Prebiotics For the Improvement Of Enzyme Activity And Phosphmentioning
confidence: 97%
“…It was observed that as compared to group A, group B and C showed the following: (1) In SD rats group C showed greater activities of sucrose and lactase in the small intestine; (2) In SD rats of group C comparative expressions of lactase gene in the anterior and posterior segments of the small intestine were increased by 1.68 and 2.26, and the Mgam gene relative expression in the posterior segment of the small intestine was improved by 0.99 in SD rats of group C; (3) the relative expressions of Na/Pi-IIb gene in the anterior and posterior segments of the small intestine were increased by 1.85 and 2.28 in SD rats of group C. These results specify that the supplementation of prebiotics in infant formula can stimulate enzyme movement in the small intestine by improving the relative expression of enzyme gene and Na/Pi-IIb gene and by reducing the intestinal injury. The polysaccharides improved to be healthier than that of oligosaccharides [124].…”
Section: Prebiotics For the Improvement Of Enzyme Activity And Phosphmentioning
confidence: 97%